Metodologia para localização de estações meteorológicas: comparação entre abordagens exata e heurística - Santos, Roberto Oliveira (2013)
This paper presents a method for planning the deployment of a network’s infrastructure for meteorological monitoring that uses the results of the numerical weather prediction MBAR as parameter for evaluating the quality of candidate solutions. The problem is addressed with the use of models for discrete location problems: the Set Covering Location Problem and Maximal Covering Location Problem. The problem of planning the structure is divided into two phases. In the ﬁrst phase, we seek to determine the minimum required a mountand location of weather stations required to meet all demand. In the second step, we seek to determine the order of installation of weather stations, maximizing the coverage area for each new installation. The proposed method is detailed, presenting the steps involved, the input and output information of each step and the changes necessary to evaluate other algorithms. A set of three scenarios was designed using the political boundaries of the State of Paraná, highways, urban areas and altimetry information. The ﬁrst scenario evaluates the ability of the approaches used to solve the Set Covering Location Problem. In the second scenario, we evaluated the ability of the approaches used to solve the Maximal Covering Location Problem and the third scenario proposes the Maximum Coverage Location Problem considering the previous existence of a monitoring network. For the solution of these problems it was compared exact and heuristic approaches. The exact approach used the method Branch & Bound for solving the problem via Mixed Integer Linear Programming. The heuristic approach used the evolutionary strategy Differential Evolution. The proposed method is distinguished by ﬂexibility for substitution of the methods used, allowing the evaluation of other techniques.